Study of multi-muon bundles in cosmic ray showers detected with the DELPHI detector at LEP - Abdallah, J; Abreu, P; Adam, W; Adzic, P; Albrecht, T; Alemany-Fernandez, R; Allmendinger, T; Allport, P; Amaldi, U; Amapane, N; Amato, S; Anashkin, E; et al. (2007)
The DELPHI detector at LEP has been used to measure multi-muon bundles originating from cosmic ray interactions with air. The cosmic events were recorded in "parasitic mode" between individual e+e- interactions and the total live time of this data taking is equivalent to 1.6 × 106 s. The DELPHI apparatus is located about 100 m underground and the 84 metres rock overburden imposes a cutoff of about 52 GeV/c on muon momenta. The data from the large volume Hadron Calorimeter allowed the muon multiplicity of 54,201 events to be reconstructed. The resulting muon multiplicity distribution is compared with the prediction of the Monte Carlo simulation based on CORSIKA/QGSJET01. The model fails to describe the abundance of high multiplicity events. The impact of QGSJET internal parameters on the results is also studied. © 2007 Elsevier B.V. All rights reserved.